2017
DOI: 10.4236/tel.2017.75083
|View full text |Cite
|
Sign up to set email alerts
|

Dividend Policy and Firm Valuation—A Study of Indian Electrical Equipment Manufacturing Industry

Abstract: Dividend policy relevance has been researched extensively, but little consensus has been built from the findings. There are many factors that affect a given firm's dividend policy which can be found in the literature such as risk faced by the firm, cash flow situation of the firm, agency costs etc. According to Bhattacharya (1979) dividend decision of a firm can be seen as a source of signal which shows that profitable firms with good project investment opportunities will pay higher dividends to present themse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…It is evident that sales growth has a negative but insignificant effect on market value of Nigerian listed manufacturing firms, which is consistent with the report of Abdolreza (2016), Ramezani et al (2002), Paminto et al (2016); while Bezawada and Tati (2017) reported a significant negative relationship. The findings of this study negates the reports of the studies of Amidu (2007), Rizqia and Sumiati (2013), Chowdhury and Chowdhury (2010) and Rehman (2016) who obtained a positive relationship between sales growth and market capitalization.…”
Section: Discussionsupporting
confidence: 88%
“…It is evident that sales growth has a negative but insignificant effect on market value of Nigerian listed manufacturing firms, which is consistent with the report of Abdolreza (2016), Ramezani et al (2002), Paminto et al (2016); while Bezawada and Tati (2017) reported a significant negative relationship. The findings of this study negates the reports of the studies of Amidu (2007), Rizqia and Sumiati (2013), Chowdhury and Chowdhury (2010) and Rehman (2016) who obtained a positive relationship between sales growth and market capitalization.…”
Section: Discussionsupporting
confidence: 88%
“…Other findings contradicting the results included: Naz and Siddiqui (2020), Farrukh et al (2017), Chaabouni (2017, and Kanakriyah (2020), who showed that dividend policy strongly affected the financial performance of firms. The non-significant effect of dividend policy on market value failed to support the results of Bezawada and Tati (2017) and De Wet and Mpinda (2013), who showed that dividend policy affects market value albeit negatively. This contradiction could perhaps be explained by using one variable to measure the dividend policy used in this study.…”
Section: Discussionmentioning
confidence: 67%
“…At the same time, Setiyowati et al (2018) confirmed the findings of De Wet and Mpinda (2013) that dividend policy affected market value, albeit negatively. According to Bezawada and Tati (2017), dividend policy had negative and non-linear effects on market value. This study focused on electrical equipment and the manufacturing industry.…”
Section: Dividend Policy and Market Valuementioning
confidence: 99%
“…It is consistent with the premise that investors favor dividends that provide a regular revenue source. (Morovvati and Pouralim2015;Bezawada & Tati, 2017;Amollo, 2016;Fajaria & Isnalita, 2018;Monoarfa, 2018;Adiputra & Hermawan, 2020;Endang et al, 2020;Hansda et al, 2020;Husain & Sunardi, 2020;Aprilyani et al, 2021;Kusumawati & Harijonom, 2021;Liviani & Rachman, 2021;Abdullah et al, 2023;Hanafi et al, 2023;Mahirun et al, 2023). However, a few studies found insignificant or adverse effects of dividend policy on firm performance (Modigliani & Miller, 1961).…”
Section: The Relation Between Dividend Policy and Firm Performancementioning
confidence: 99%